Physical concept and calculation of boiling point in a pulsating heat pipe - A. N. Naumova; V. Yu. Kravets; Yu. Ye. Nikolaenko (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
LED development is accompanied by the need to ensure a constructive solution for the thermal conditions' problem. For this purpose one can use pulsating heat pipes (PHP), that operate more efficiently after the start of heat carrier boiling. This article describes the physical representation and formula that allows determining the boiling point, which is a lower bound of the PHP effective operating range. It is shown that the main factors influencing the required heat flow are driving capillary pressure and velocity of the vapour bubble. The formula was obtained for the closed PHP made of the copper with water as a heat carrier. Information about this heat flux can be used for further design of cooling systems for heat-sensitive elements, such as LED for promising lighting devices.